The relationship between ABO blood types and clopidogrel-related low on-treatment platelet reactivity in patients with coronary artery diseases and type 2 diabetes mellitus: a secondary analysis of a prospective cohort study - Menglu Liu; Jiawen Li; Kailun Yan; Kexin Zhang; Pei Zhu; Xiaofang Tang; Deshan Yuan; Yuejin Yang; Runlin Gao; Jinqing Yuan; Xueyan Zhao (Diabetology & Metabolic Syndrome)
Abstract Background The risk of bleeding associated with antiplatelet therapy in patients with coronary artery disease (CAD) has received a lot of attention. The aim of this study was to investigate the relationship between ABO blood system and low on-treatment platelet reactivity (LTPR) in patients with CAD and type 2 diabetes mellitus (T2DM). Methods This study examined 10,724 consecutive patients who received percutaneous coronary intervention in China between January and December in 2013 and applied logistic regression to assess the association between ABO blood types and LTPR. These patients who were diagnosed with T2DM, had thromboelastogram (TEG) results and were administered clopidogrel were ultimately enrolled. LTPR is defined by a platelet maximum amplitude of < 31 mm on TEG, induced by adenosine diphosphate. Results Among 3,039 patients (mean age, 59.35 ± 9.89; male, 74.60%), 1,089 (35.83%) presented with LTPR. Multivariate logistic regression revealed that blood type O was independently related to higher odds of LTPR (OR O vs. Non−O: 1.298, 95% CI 1.099–1.534) and that blood type A was independently related to lower odds of LTPR (OR A vs. Non−A: 0.804, 95% CI 0.674–0.958). For further analysis, multivariate logistic regression revealed that, compared to blood type A, type O was independently related to higher odds of LTPR (OR O vs. A: 1.409, 95% CI 1.147–1.729). Conclusions This study reported that in patients with CAD and T2DM, blood type O was independently associated with higher odds of LTPR, indicating a greater likelihood of bleeding, while blood type A was independently related to lower odds of LTPR, suggesting a reduced likelihood of bleeding.